First and Second-Order Theory of Mind as Predictors of Cooperative Behaviors in Preschool and School Children - Rubio, Fernanda; Neira, Catherine; Villacura-Herrera, César; Castillo, Ramón D. (Psykhe, 2022)
Prosocial behavior in childhood has been widely studied over the last decades. However, the cognitive processes underlying the development of these behaviors and how children understand each other are still not entirely clear. The concept of Theory of Mind (ToM) has become particularly relevant in the study of the development of social abilities in childhood. In this study, we hypothesize that the cognitive processes of first and second-order ToM are able to predict prosocial behaviors in a differentiated manner. A total of 40 children aged 3 to 7 years old (M = 5.075; SD = 1.248) were evaluated on different tasks to measure both ToM skills, as well as prosocial behaviors such as helping (Instrumental Help; IH) and cooperating (measured through Cooperative Problem Solving and Cooperative Gaming; CPS & CG respectively). Cooperative behavior-related tasks were performed under two conditions: Firstly, a condition of General Behavior (GB) where the task was performed normally. Then, a condition that included an Interruption Period (IP) where the task was abruptly interrupted to assess if the prosocial behavior was resumed autonomously by the child. Our findings enable us to propose a potential framework where first-order ToM predicts basic helping behaviors, while second-order ToM predicts more complex cooperative behaviors. These results also demonstrate that first and second-order ToM skills can differentially predict the complexity of children's prosocial behavior and that helping and cooperative behaviors could be regulated by differential processes.